Incidence and antimicrobial profile of extended-spectrum β-lactamase producing gram-negative bacterial isolates: An in-vitro and statistical analysis - Turki M.S. Dawoud; Asad Syed; Amit Kumar Maurya; Syed Sayeed Ahmad; Quazzafi Rabbani; Abdullah A. Alyousef; Abdulaziz Alqasim; Mohammed Arshad; Mohd Sajid Khan; Mohammad Khalid; Haroon Khan; Maria Daglia (Elsevier, 2020)
Objectives: There is an extensive incidence of extended-spectrum beta-lactamases (ESBLs), principally in the hospital environment across the world. The present study was designed to discover the frequency of ESBL-production among the clinical isolates of Escherichia coli, Klebsiella pneumonia, and Pseudomonas aeruginosa. The study also focused on determining their liability to the selected antimicrobials. Methods: Two hundred ten (210) clinical specimens were tested for the occurrence of ESBL using the double-disc synergy test. The molecular, physicochemical, absorption, distribution, metabolism, excretion, and toxicity were checked through an online server. Results: Among the screened clinical isolates, E. coli (n = 44), K. pneumonia (n = 34) and P. aeruginosa (n = 14) were ESBL markers. The ESBL producing isolates exhibited co-resistance to diverse categories of antibiotics. It was observed that all the ESBL-producing isolates were sensitive towards imipenem and faropenem with minimal proportion of resistance. Conclusion: The imipenem and faropenem can be recommended as the drugs of selection due to a lesser amount of resistance as compared to other antibiotics in this study.